1999
DOI: 10.1016/s0042-6989(98)00162-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived distance, shape and size

Abstract: If distance, shape and size are judged independently from the retinal and extra-retinal information at hand, different kinds of information can be expected to dominate each judgement, so that errors in one judgement need not be consistent with errors in other judgements. In order to evaluate how independent these three judgments are, we examined how adding information that improves one judgement influences the others. Subjects adjusted the size and the global shape of a computer-simulated ellipsoid to match a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 40 publications
10
72
0
Order By: Relevance
“…For example, Johnston, Cumming and Landy [17] found that people form a weighted average of motion and disparity signals when asked to report an object's shape. The same is true for texture and disparity signals to depth [18], for the visual perception of slant [19], for the judgment of texture-defined edges [20], and for the estimate of distance [21]. More importantly, Young et al [18], among others, showed that the weights change in the predicted direction as signal reliability is manipulated.…”
Section: Weighting Of Sensory Informationmentioning
confidence: 87%
“…For example, Johnston, Cumming and Landy [17] found that people form a weighted average of motion and disparity signals when asked to report an object's shape. The same is true for texture and disparity signals to depth [18], for the visual perception of slant [19], for the judgment of texture-defined edges [20], and for the estimate of distance [21]. More importantly, Young et al [18], among others, showed that the weights change in the predicted direction as signal reliability is manipulated.…”
Section: Weighting Of Sensory Informationmentioning
confidence: 87%
“…For the perceived shape of the cylinders, the errors that we expect to see are compressions or expansions of depth extents (Brenner and Van Damme 1999;Johnston 1991;Todd et al 1995). The visual information about the shape and orientation of the cylinders is primarily contained in the contours of the top and bottom edges, stereopsis and motion parallax.…”
Section: Discussionmentioning
confidence: 97%
“…We suspected that the systematic deviations were due partly to a deformation of perceived shape. If so, we could expect an interaction between the distance of the cylinder from the observer and its shape, because the perceived depth (along the line of sight) is a non-linear function of distance (Brenner and Van Damme 1999;Johnston 1991;Todd et al 1995). However, the systematic deviations did not depend on either the cylinder's aspect ratio or its distance from the observer.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Separate independent processing for different judgments can result in substantial conf1icts between them (Abrams & Landgraf 1990;Glennerster et al 1996;Mack et al 1985). Nevertheless, the separation seems be so complete that we even fail to notice conflicts between attributes when the conflicts themselves could give us valuable additional information (Brenner & Damme 1999;Brenner & Landy 1999). The main reason for our judgments normally being approximately consistent is presumably the consistency in the world "outside," in what S&B call the "global array.…”
Section: We Are Better Off Without Perfect Perceptionmentioning
confidence: 90%